A review of objective structured practical examination (OSPE) in pharmacology at a rural medical college - Deshpande, Rushikesh P.; Motghare, Vijay M.; Padwal, Sudhir L.; Bhamare, Chetanraj G.; Rathod, Suvarna S.; Pore, Rakesh R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: 1. To evaluate the attitudes of undergraduate medical students towards objectively structured practical examination (OSPE) component of Pharmacology practical examination. 2. To investigate any gender differences and any influence of medium of instruction in school on these attitudes. Methods: The scores of 40 undergraduate medical students were analysed at S R T R Government Medical College, Ambajogai, Maharashtra, India. A Likert scale containing 9 items was used to assess the attitudes of students towards OSPE in Pharmacology. Student perspectives regarding the OSPE were obtained by asking them to respond to a questionnaire. Results: The study revealed that the OSPE was an acceptable tool in Pharmacology practical examination. The overall mean attitude score was 3.99. The response of male students towards OSPE (4.2) was more favourable as compared to that of female students (3.9) Students strongly agreed that OPSE covers wide range of skills and it is a good form of examination and learning experience. Majority of students were in favour of continuing OSPE as a method for examination in Pharmacology. Conclusions: OSPE was found to be a valuable tool to check the depth of understanding of undergraduate students. OSPE can be used as an index of the learning attitude of students. The present study is a small step in a direction of changing the traditional patterns of practical examination to a more objective and reliable way of evaluation in Pharmacology. It will help in modifying teaching-learning strategies so that both, the teachers as well as the students can gain maximum advantage.